2017
DOI: 10.1140/epjc/s10052-017-5396-2
|View full text |Cite
|
Sign up to set email alerts
|

Bouncing cosmology from warped extra dimensional scenario

Abstract: From the perspective of four dimensional effective theory on a two brane warped geometry model, we examine the possibility of "bouncing phenomena"on our visible brane. Our results reveal that the presence of a warped extra dimension lead to a non-singular bounce on the brane scale factor and hence can remove the "big-bang singularity". We also examine the possible parametric regions for which this bouncing is possible.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…However the inequality in eqn. (59) is valid in the regime R > 0 i.e for entire cosmic time. This indicates that the linear order perturbation theory is valid in the entire range of cosmic time in the ghost free F (R, G) bouncing model.…”
Section: A Scalar Perturbationsmentioning
confidence: 99%
“…However the inequality in eqn. (59) is valid in the regime R > 0 i.e for entire cosmic time. This indicates that the linear order perturbation theory is valid in the entire range of cosmic time in the ghost free F (R, G) bouncing model.…”
Section: A Scalar Perturbationsmentioning
confidence: 99%
“…( 31) denote the solutions of A(ϕ) and Ψ(ϕ) respectively, while the scalar field potential Ṽ (Ψ) is reconstructed in Eq. (32). It is important to note that γ < 0 is not allowed as this makes the bulk scalar field complex (Eq.…”
Section: The Forms Of Bulk Scalar Field Its Potential and The Effecti...mentioning
confidence: 99%
“…It was further shown that the radion kinetic term in such a scenario has a non-canonical coupling which exhibits a phantom character for certain values of the modulus. This makes it a suitable candidate to explain several early universe scenarios [30][31][32] (for bouncing cosmology and the violation of energy condition, see [33,34]). Particularly, in a FRW background the negative kinetic term of the radion leads to a violation of the null energy condition making it viable for a bouncing universe [31].…”
Section: Introductionmentioning
confidence: 99%
“…Here it may be mentioned that a bulk massive scalar field or higher curvature term(s) in the bulk can generate such stable modulus potential and thus may act as suitable stabilizing agent in the braneworld model [87,88]. This resulted into a large volume of work on phenomenological and cosmological implications of warped geometry model [89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106]. However in the context of cosmology in the braneworld scenario, one needs to incorporate dynamical stabilization mechanism of the interbrane separation.…”
Section: Introductionmentioning
confidence: 99%